Tratamento de efluente de indústria têxtil por reator biológico com leito móvel - Soler, Cassio Renato (2013)
The environment contamination caused by the textile sector has a special meaning due to volumes of wastewater. The biological treatments most commonly used by textile industries are biofilters and activated sludge, both with a high financial cost for industries with chemicals products and the need for sludge disposal. This work studied the viability of treatment of textile effluent´s by MBBR "Moving Bed Biofilm Reactor". This process combines the benefits of treatments mentioned above and at the same time reduces undesirable characteristics of high sludge generation, hydraulic retention time and solids loss. The effluent was characterized as COD, BOD5, spectral area, total suspended solids, volatile suspended solids and toxicity before and after treatment. The treatment of the effluent occurred in different organic loading rates from 0.3 gCOD/L.d up to 9.0 g COD/L.d with 4 stages: adaptation 0.3gCOD/L.d and others 3 stages 1.2gCOD/L, 3.0 gCOD/L and 9.0gCOD/L.d. This reactor was operated for 107 days, reaching 65% removal of COD, 94% of BOD5, 58% of spectral area, 82% of TSS and 87% of toxicity. The results were evaluated by ANOVA with Tukey's test at 0.05 significance level. The calculated kinetics of the process presented consumption specific maximum of substrate of 0,027d-1, compatible with biological treatment effluent with recalcitrant content. Through these analyzes it was verified that the best removing results were achieved when the reactor was operated at lower OLRs.